Canine acral lick dermatitis syndrome - GIANNOULOPOULOS (Γ.Δ. ΓΙΑΝΝΟΥΛΟΠΟΥΛΟΣ), G. D.; SARIDOMICHELAKIS (Μ.Δ. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Canine acrai lick dermatitis is a complicated and challenging syndrome occurring in companion animal dermatology. Skin lesions are caused by intense and prolonged licking of a localized area, usually on the lower parts of the limbs that progressively may result in plaque or nodule formation with alopecia, erythema, hyperpigmentation, exudation,erosion and ulceration. Aerai lick dermatitis develops more often in male dogs of large breeds and has a multifactorial aetiology. The underlying causes may be broadly separated into organic (e.g., pruritic skin diseases, painful conditions) and psychogenic. The former subset includes mainly deep bacterial pyoderma, atopic dermatitis, food allergy, foreign bodies, sensory neuropathies and painful bone and articular diseases. The psychogenic subset may be either a primary (e.g., the result of long-standing anxiety, boredom, attention-seeking or stereotypic behavior) or a psychosomatic behavioural abnormality. Regardless of the aetiology and the primary role it may play, the most common complication in the psychogenic aerai lick dermatitis is actually the deep bacterial pyoderma observed in the majority of the cases. Diagnosis of the disorder is reached after exclusion of similar-looking skin diseases, such as ringworm kerion, demodicosis, leishmaniosis, sterile granulomas and neoplasia. An extensive list of diagnostic tests is necessary to identify the underlying cause(s) and includes cytological examination, bacterial culture and antibiotic susceptibility testing, histopathological examination, imaging of the affected area and hypoallergenic food trial. A prerequisite to diagnosing the psychogenic subset of the disease is to rule-out potential organic causes, coupled with persistence of skin licking, despite resolution of deep bacterial pyoderma. Regardless of the underlying cause, therapy should always include mechanical restrain, as well as the long-term topical and systemic use of antimicrobials that ideally should be selected based on the results of antimicrobial susceptibility testing. Specific treatment in also warranted to resolve potential organic causes of the syndrome, whereas, management of its psychogenic subset should be based on avoidance of the causative and triggering factors, desensitization and counter conditioning, along with the administration of psychotropic medication. Alternative therapeutic modalities, considered supplementary or employed when everything else fails, may include topical glucocorticoids, dimethyl sulfoxide, capsaicin or tacrolimus, as well as cryosurgery, laser surgery, acupuncture or radiation therapy.